2022
DOI: 10.1111/ejn.15573
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory responses in a belt region of the dorsal auditory cortical pathway

Abstract: A basic function of the cerebral cortex is to receive and integrate information from different sensory modalities into a comprehensive percept of the environment. Neurons that demonstrate multisensory convergence occur across the necortex but are especially prevalent in higher order association areas. However, a recent study of a cat higher order auditory area, the dorsal zone (DZ) of auditory cortex, did not observe any multisensory features. Therefore, the goal of the present investigation was to address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 90 publications
3
12
0
Order By: Relevance
“…One of the major goals of the present study was to compare multisensory processing in A1, a core auditory area, with that found in area DZ, which is a higher-order region of the auditory cortical belt. The present results (and previous studies: Bizley et al 2007 ; Bizley and King 2009 ; Meredith and Allman 2015 ; Merrikhi et al. 2022 ) show that multisensory processing occurs at the neuronal level in both A1 and in DZ.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One of the major goals of the present study was to compare multisensory processing in A1, a core auditory area, with that found in area DZ, which is a higher-order region of the auditory cortical belt. The present results (and previous studies: Bizley et al 2007 ; Bizley and King 2009 ; Meredith and Allman 2015 ; Merrikhi et al. 2022 ) show that multisensory processing occurs at the neuronal level in both A1 and in DZ.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, bimodal multisensory neurons were predominant in DZ, where 68.9% of neurons showed multisensory properties. In the context of the anatomical distribution of the different neuron response types, while the several of the neuron classes showed a differential anatomical distribution in DZ ( Merrikhi et al. 2022 ), such anatomical organizational effects were not demonstrated for A1.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is possible that the different inhibitory cell types show different degrees of MSI or may show region‐specific properties. In contrast to the PV neurons in the rodent RL area (Olcese et al, 2013), inhibitory neurons in the dorsal zone of the cat auditory cortex exhibited similar degrees of MS enhancement than excitatory ones (Merrikhi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multisensory neurons can respond to multisensory stimulation without exhibiting MSI, but with responses that fail to achieve a statistically significant difference from their most effective unisensory response (e.g., see (Perrault Jr et al , 2005)). Such non-significant response changes, however, can contribute to substantial effects at the population level (Merrikhi et al , 2022a;Merrikhi et al , 2022b) although their developmental presentation is not known. Furthermore, the AES area is a conglomerate region consisting of 3 different sensory representations, each with their own connectional features and functional properties (for review, see (Meredith et al , 2018)).…”
Section: Introductionmentioning
confidence: 99%